Development, characterization and efficiency of nitrogen fertilizer associated with molybdenum nanoparticles - Moreira, Lílian Angélica (2022)
Nitrogen (N) use efficiency is directly associated with sustainable agriculture. The use of renewable energy sources and increase in productivity have increased the amountof fertilizers used and strategies to improve their use are required. Among the strategies to increase the efficiency of N fertilizers are the use of urease inhibitors, nitrification inhibitors, addition of micronutrients, polymers, among others. Therefore, the molybdenum (Mo) addition is a promising alternative due to its potential to influence N metabolism in plants and its utilization, and Mo can be supplied as soluble sources (ammonium molybdate) or as nanoparticles (Mo trioxide). Studies were conducted to evaluate the interaction between Mo sources, urea and N-(n-butyl) thiophosphoric triamide (NBPT) on physical-chemical characteristics, ammonia (NH3) volatilization, recovery of 15N by sugarcane and metabolism and N uptake by corn in nutrient solution. Mo sources were granulated with urea, whereas NBPT was treated as a cover. After fertilizers characterization it was found that Mo reacts with NBPT, eliminating its effect as a urease inhibitor. The N- NH3 losses of urea + NBPT were close to 44% of the N applied, while only urea + NBPT reached 33%. Then, the fertilizer with best physical-chemical characteristics were selected among the mixtures of urea and Mo, using the average rate 600 g of Mo per 100 kg-1 of N, as the appropriate one to proceed with the evaluations that consisted of applying the fertilizer to sugarcane seedlings. At this point, the recovery of 15N-urea by sugarcane was evaluated and it was observed that there was no change as a function of the source and addition of Mo, with an overal recovey of 80% by the plant. The biomass production and N content were also not influenced, presenting the average of 408 g pot-1 and 3.8 g pot-1. In order to evaluate the metabolic changes and the uptake preference of N forms as a function of Mo addition, an experiment was conducted with corn under controlled conditions. The treatments consisted of the omission of Mo and N and the supply of these nutrients 28 days after transplanting the seedlings into a nutrient solution. It was verified that the Mo added to the nutrient solution after 28 days resulted in similar productivity as the treatments with N and Mo, approximately 215 g pot-1. In this condition it was also observed that in the absence of Mo and supply of N the plants absorbed a greater amount of ammonium, proving that Mo favors nitrate absorption. The finding is that the addition of Mo to urea is a feasible strategy of uniform distribution of the nutrient in crops, but with no potential in affecting the metabolsim of the recovery of N by the plant.